Vehicular Ad hoc Network for Intelligent Transport System: A review - Saad Talib, Mohammed; Hassan, Aslinda; Hussin, Burairah; Abdul-Jabbar Mohammed, Ali; Abdulhussian Hassan, Ali; Awad Mutlag, Ammar (International Journal of Engineering and Technology, 2018)
the numbers of accidents are increasing in an exponential manner with the growing of vehicles numbers on roads in recent years.  This huge number of vehicles increases the traffic congestion rates. Therefore, new technologies are so important to reduce the victims in the roads and improve the traffic safety. The Intelligent Transportation Systems (ITS) represents an emerging technology to improve the road's safety and traffic efficiency. ITS have various safety and not safety applications. Numerous methods are intended to develop the smart transport systems. The crucial form is the Vehicular Ad hoc Networks (VANET). VANET is becoming the most common network in ITS. It confirms human’s safety on streets by dissemination protection messages among vehicles. Optimizing the traffic management operations represent an urgent issue in this era a according to the massive growing in number of circulating vehicles, traffic congestions and road accidents. Street congestions can have significant negative impact on the life quality, passenger's safety, daily activities, economic and environmental for citizens and organizations. Current progresses in communication and computing paradigms fetched the improvement of inclusive intelligent devices equipped with wireless communication capability and high efficiency processors.